Perbedaan Penggunaan Distraksi (Mendengarkan Musik) dan Nafas dalam Terhadap Tingkat Kecemasan pada Ibu Pre Operasi Seksio Sesaria di Ruang Kebidanan Rsia Tiara Kabupaten Tangerang - Rahmawati, Silvia Anggraeni; Barkah, Asep (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Mothers who give birth by caesarean section not only cause physical disturbances but also cause psychological disorders, one of which causes anxiety. One effort to deal with anxiety is by using distraction (listening to music) and deep breathing. Knowing the differences in the use of distraction (listening to music) and deep breathing on the level of anxiety in preoperative cesarean section mothers in the Midwifery Room of RSIA Tiara, Tangerang Regency. Quasy experimental design with pretest-posttest design with control group design. The sample consisted of 40 mothers who wanted to give birth by elective SC in the Midwifery Room of RSIA Tiara, Tangerang Regency, with a total of 40 people using a purposive sampling technique. The intervention was given music therapy for 30 minutes and deep breathing therapy for 10 minutes. Bivariate analysis used paired simple t test and independent t test. The results of a univariate study of preoperative maternal anxiety before cesarean section before administration of the distraction method (listening to music) were mostly moderate 90.0% and after mild 85.0%. anxiety in preoperative cesarean section mothers before deep breathing therapy was mostly moderate 95.0% and after mild 95.0%. The bivariate results of the paired simple t test were 0.000 and the independent posttest t test obtained a p value = 0.841. There is no difference in the use of distraction (listening to music) and deep breathing on the level of anxiety in preoperative cesarean section mothers. Pre-cesarean birth mothers are expected to be able to listen to music or apply deep breathing relaxation techniques when dealing with anxiety in order to create a sense of comfort. Keywords: Distraction (Listening to Music), Deep Breathing, Anxiety Level, Pre-Operational Caesarean Section  ABSTRAK Ibu melahirkan dengan tindakan seksio sesaria  tidak saja menimbulkan gangguan fisik juga menimbulkan gangguan psikologis salah satunya menimbulkan kecemasan. Salah satu upaya untuk menangani kecemasan diantaranya dengan penggunaan distraksi (mendengarkan musik) dan nafas dalam. Mengetahui perbedaan penggunaan distraksi (mendengarkan musik) dan nafas dalam terhadap tingkat kecemasan pada ibu pre operasi seksio sesaria di Ruang Kebidanan RSIA Tiara Kabupaten Tangerang. Quasy eksperimental desain dengan rancangan pretest-posttest with control group design. Sampel adalah ibu yang mau melahirkan secara SC elektif di Ruang Kebidanan RSIA Tiara Kabupaten Tangerang pada bulan Mei berjumlah 40 orang dengan teknik purposive sampling. Intervensi diberikan terapi musik selama 30 menit dan terapi nafas dalam selama 10 menit. Analisis bivariat menggunakan uji paired simple t test dan t test independent. Hasil penelitian univariat kecemasan ibu pre operasi seksio sesaria sebelum pemberian metode distraksi (mendengarkan musik) sebagian besar sedang 90,0% dan sesudah ringan 85,0%. kecemasan pada ibu pre operasi seksio sesaria sebelum terapi nafas dalam sebagian besar sedang 95,0% dan sesudah ringan 95,0%. Hasil penelitian bivariat uji paired simple t test sebesar 0,000 dan uji t test independent posttest didapatkan nilai p value = 0,841. Tidak ada perbedaan penggunaan distraksi (mendengarkan musik) dan nafas dalam terhadap tingkat kecemasan pada ibu pre operasi seksio sesaria. Ibu bersalin pre operasi sesarea diharapkan dapat mendengarkan musik atau menerapkan teknik relaksasi nafas dalam saat menghadapi kecemasan agar dapat menciptakan rasa nyaman. Kata Kunci: Distraksi (Mendengarkan Musik), Nafas Dalam, Tingkat Kecemasan, Pre Operasi Seksio Sesaria